Women’s health beliefs and breast cancer screening practices in Nigeria (2012)
Receiving a diagnosis of breast cancer and coping with subsequent treatments can be highly threatening experiences that may influence women’s breast screening practices. It is therefore important to have a good understanding of women’s beliefs and behaviour where breast cancer may be concerned. This study examined the influence of women’s beliefs on breast screening practices (BSE) in four rural communities of Nigeria. Utilizing cross-sectional design, women’s beliefs were measured using the Health Belief Model (HBM) scale adapted to Nigerian cultural settings. Women’s perceived risk to breast cancer was found to be moderately high. Self-confidence and intention to participate in health-promoting behaviours were the significant variables that influenced the women’s practice of BSE (P = 0.000 and P = 0.021 respectively). The authors therefore recommend that community health nurses should promote activities geared towards mastery of BSE by promoting self -confidence in women through regular demonstration and reinforcement of health educational sessions at the primary health care level